2016
DOI: 10.1167/iovs-16-20648
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Hemodynamics Seen on Optical Coherence Tomography Angiography Before and After Treatment of Retinal Vein Occlusion

Abstract: Optical coherence tomography angiography can evaluate the retinal hemodynamics in patients with RVOs. Anti-VEGF therapy reduced the NPA size and improved retinal blood flow, especially in the retinal deep layer. The current results suggested that anti-VEGF therapy might improve retinal deep ischemia in patients with RVO in the retinal deep layer, which is abundant in capillaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
66
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 27 publications
6
66
0
1
Order By: Relevance
“…Although we did not find any case of complete reperfusion after anti-VEGF therapy within the area of coexisting edema and nonperfusion, the retinal perfusion may be improved with resolution of the edema in some cases. Suzuki et al 28 have reported decreased nonperfusion after anti-VEGF therapy in patients with RVO. de Carlo et al 39 also have reported the reappearance of retinal microvasculature after anti-VEGF treatment in the areas previously shown to have flow voids due to intraretinal fluid in diabetic macular edema (DME).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although we did not find any case of complete reperfusion after anti-VEGF therapy within the area of coexisting edema and nonperfusion, the retinal perfusion may be improved with resolution of the edema in some cases. Suzuki et al 28 have reported decreased nonperfusion after anti-VEGF therapy in patients with RVO. de Carlo et al 39 also have reported the reappearance of retinal microvasculature after anti-VEGF treatment in the areas previously shown to have flow voids due to intraretinal fluid in diabetic macular edema (DME).…”
Section: Discussionmentioning
confidence: 98%
“…To date, several studies have reported the macular VD and FAZ before and after anti-VEGF therapy. [28][29][30] However, the results are conflicting because of the short follow-up periods and a limited number of patients studied. In addition, the possible associations between changes in the retinal VD and visual outcomes have not been reported.…”
mentioning
confidence: 99%
“…The innovative data provided by OCTA was the involvement of DCP [1, 17, 18]. On standard fluorescein angiography, it is impossible to identify the exact location of capillary leakage, and the DCP is not directly visible.…”
Section: Discussionmentioning
confidence: 99%
“…On standard fluorescein angiography, it is impossible to identify the exact location of capillary leakage, and the DCP is not directly visible. With the advent of OCTA, it was possible to visualize the presence of cysts, the non-perfusion areas, the dilation of macular capillaries, and the disruption of perifoveal arcade at the level of SCP and DCP [1, 5, 17]. The reduction of VD in DCP was correlated with a degree of peripheral ischemia, evaluated by means of fluorescein angiography [18].…”
Section: Discussionmentioning
confidence: 99%
“…Выделены зоны снижения плотности капиллярной сети (овал), которые не визуализировались при проведении флюоресцентной ангиографии, и расширение ава-скулярной зоны (стрелка) Более выраженные микроциркуляторные из-менения характерны для ОЦВС, что ассоциирует-ся с более высокими концентрациями эндотели-ального сосудистого фактора роста (VEGF) [4,5]. N. Suzuki et al [25] определили, что терапия ин-гибиторами ангиогенеза уменьшает площадь зон отсутствия капиллярной перфузии, а количество интравитреальных инъекций по данным ОКТ-ангиографии прямо пропорционально улучшению гемодинамики.…”
Section: Discussionunclassified